2020
DOI: 10.1080/07399332.2020.1842878
|View full text |Cite
|
Sign up to set email alerts
|

Determination of exercise habits, physical activity level and anxiety level of postmenopausal women during COVID-19 pandemic

Abstract: In this study, researchers aimed to determine exercise habits, physical activity (PA) levels and anxiety levels of postmenopausal women (PMw) during the self-quarantine period of the COVID-19 pandemic. 104 PMw (59.00 ± 6.61 years old) participated in the study. It was found that PMw who had exercise habits before the pandemic period had higher PA levels, and the women with high anxiety levels during the pandemic had lower PA levels (p < .05). Anxiety levels and PA were negatively associated with each other. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Five studies exclusively reported on changes in dietary behaviors in older individuals [ 12 , 18 , 26 , 27 , 31 ], 17 exclusively reported on changes in physical activity [ 13 - 17 , 19 , 22 , 23 , 25 , 28 - 30 , 33 - 35 , 37 , 38 ], and 5 reported on both [ 20 , 21 , 24 , 32 , 36 ]. Many (n = 17) studies reported on a variety of diet and/or physical activity outcomes for the total study population but provided only selective results for the specified age group of 50+ years [ 12 , 14 , 16 , 17 , 19 - 25 , 27 , 29 , 31 , 32 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies exclusively reported on changes in dietary behaviors in older individuals [ 12 , 18 , 26 , 27 , 31 ], 17 exclusively reported on changes in physical activity [ 13 - 17 , 19 , 22 , 23 , 25 , 28 - 30 , 33 - 35 , 37 , 38 ], and 5 reported on both [ 20 , 21 , 24 , 32 , 36 ]. Many (n = 17) studies reported on a variety of diet and/or physical activity outcomes for the total study population but provided only selective results for the specified age group of 50+ years [ 12 , 14 , 16 , 17 , 19 - 25 , 27 , 29 , 31 , 32 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior behaviour and, more specifically, habits were associated with PA engagement during the periods of restrictions [23,28,30,31,37,42,57,67,75,78]. It is, however, apparent that relationships and interactions between factors from different levels of the socioecological model and the magnitude of effect that these may have at an individual level may, at least in part, explain some of the variations in the behaviour observed.…”
Section: Discussionmentioning
confidence: 96%
“…Correlations were identified with anxiety, depression/mood, and emotions. For anxiety, higher levels were associated with decreased or less PA [23,35,41,56,61,71,74,80] and outdoor activity [49], whilst lower levels were associated with participating in physical exercise [48,74] and achieving recommended PA guidelines [53]. Further, non-directional, significant interactions were also reported [26,63].…”
Section: Mental Healthmentioning
confidence: 95%
See 2 more Smart Citations